Molecular Rhodium Complex within N-Rich Porous Polymer Macroligand as Heterogeneous Catalyst for the Visible-Light Driven CO2 Photoreduction - Newar, Rajashree; Ghosh, Ashta C.; Kumari Riddhi, Riddhi; Rajapaksha, Rémy; Samanta, Partha; Wisser, Florian M.; Canivet, Jérôme (Advanced Energy and Sustainability Research, 2023)
The heterogenization of molecular catalysts within a porous solid acting as macroligand can advantageously open access to enhanced stability and productivity, and thus to more sustainable catalytic process. Herein, a porous organic polymer (POP) made through metal-free polymerization using bipyridine repeating units is reported. This N-rich POP is an efficient macroligand for the heterogenization of molecular rhodium complexes. The intrinsic catalytic activity of the heterogenized catalyst is slightly higher than that of its homogeneous molecular counterpart for formic acid production as a unique carbon-containing product. The heterogenization of the rhodium catalysts enables recycling for a total productivity of up to 8.3 g of formic acid per gram of catalyst after 7 reuses using visible light as the sole energy source.
CRIS-Team Scopus Importer:2023-12-08
Keywords: carbon dioxide reduction; macroligands; photocatalysis; porous organic polymers; rhodium complexes